2000
DOI: 10.1046/j.1365-2362.2000.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cholesterol lowering on carotid and femoral artery wall stiffness and thickness in patients with familial hypercholesterolaemia

Abstract: One year of cholesterol lowering therapy in FH decreases the wall stiffness in the CFA and the arterial wall thickness in the CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 35 publications
3
58
0
1
Order By: Relevance
“…The data for beta-blockers are not nearly as clear. Drugs that have favourable effects on outcomes and endothelial function, such as statins, have been shown to decrease arterial stiffness, but further studies are needed in this area (45,46).…”
Section: Relationship Of Arterial Stiffness To Risk Factors and Theirmentioning
confidence: 99%
“…The data for beta-blockers are not nearly as clear. Drugs that have favourable effects on outcomes and endothelial function, such as statins, have been shown to decrease arterial stiffness, but further studies are needed in this area (45,46).…”
Section: Relationship Of Arterial Stiffness To Risk Factors and Theirmentioning
confidence: 99%
“…Regardless of the interpretation, our study identified elevated RI as an independent predictor of GFR 1 yr after transplantation in recipients with normal histologic findings and with no history of rejection. This observation highlights the potential importance of elevated RI in identifying a group of transplant patients who are at risk for early loss of kidney function and might benefit from therapeutic interventions, possibly directed toward improving vascular compliance (32). Is the loss of circadian BP rhythm a pathogenic factor involved in allograft function loss?…”
Section: Discussionmentioning
confidence: 86%
“…Cholesterol lowering has been shown to improve arterial compliance in patients with familial hypercholesterolemia (Tomochika et al, 1996;Smilde et al, 2000) and hypertension (Ferrier et al, 2002). Stanol ester margarine lowers serum total and LDL cholesterol concentrations (Law 2000).…”
Section: Discussionmentioning
confidence: 99%